Analysis of the Effect of Perceived Benefit, Electronic Word of Mouth and Perceived Web Quality on Online Purchase Intention with Trust as an Intervening Variable in Surakarta - Wulandari, Reyza; Susila, Ihwan (Ekonomi Bisnis, 2024)
Rapid advancements in information technology and the internet have revolutionized global business, making the exchange of goods and services online, driving dynamic business models such as Business-to-Consumer (B2C), which allows companies to offer their products online through smartphones that can be accessed anytime and anywhere. The surge in online shopping offerings forces entrepreneurs to rigorously assess the functionality and user benefits of their online platforms. This study aims to analyze the effect of perceived benefits, electronic word of mouth, and perceived web quality on online purchase intentions at Shopee, with trust as an intervening variable in Surakarta. The data collected were 129 respondents aged 18-35 years using a purposive sampling technique. The data was then analyzed using Smart PLS 3.0. The results showed that perceived web quality has a positive and significant effect on perceived benefits, perceived web quality has a positive and significant effect on eWOM, perceived web quality has a positive and significant effect on trust, perceived web quality positively and significantly influences online purchase intentions, trust positively and significantly impacts perceived web quality, with eWOM acting as a mediating factor, perceived benefit has a positive and significant effect on online purchase intentions, and perceived web quality has a positive and significant effect on online purchase intentions, with trust acting as a mediating variable.